Seeing with the Customer's Eye: Exploring the Challenges and Opportunities of AR Advertising. Issue 2 (14th March 2020) - de Ruyter, Ko; Heller, Jonas; Hilken, Tim; Chylinski, Matthew; Keeling, Debbie I.; Mahr, Dominik
Abstract : This position article on augmented reality (AR) advertising offers a conceptual framework of recent scholarship on the intersection between AR technologies, advertising, and marketing metrics. The framework identifies theory-based building blocks for this domain alongside relevant recent examples. It proposes a conceptual case for contextualization of advertising content through AR technology. Finally, an agenda for future research in AR advertising is specified, incorporating multiple conceptual perspectives and empirical directions.